Synthesis of 1, 2, 3‐Triazole‐4‐carboxamide‐Containing Foldamers for Sulfate Recognition. Issue 13 (27th February 2014) - Cao, Li; Jiang, Runsheng; Zhu, Yulan; Wang, Xinlong; Li, Yongjun; Li, Yuliang
Abstract: A series of triazolecarboxamide‐containing foldamers were synthesized from simple starting materials by means of repeated [3+2] cycloadditions) and acid–amine coupling reactions. Foldamer–anion binding behavior and affinities were determined by 1 H NMR titration in [D2 ]dichloromethane. The selective recognition of sulfate by these motifs was studied by one‐ and two‐dimensional ( 1 H, 1 H‐ 1 H COSY and NOESY) NMR spectroscopy as well as UV/Visible and fluorescence titrations. The structures of the triazolecarboxamide‐containing foldamers can be optimized for highly selective recognition of sulfate anions by changing the numbers of triazolecarboxamide units and by the introduction of electron‐withdrawing substituents on the terminal benzene ring. These findings indicate the importance of the structural compatibility between the receptor and anions for the highly selective anion binding as well as the electronic effect on tuning the anion‐binding affinities of receptors. Abstract : A series of triazolecarboxamide‐containing foldamers were synthesized. By increasing the numbers of triazolecarboxamide units and modification of the terminal benzene ring, the binding stoichiometry and binding affinity can be controlled.